Glycolysis and the Pentose Phosphate Pathway after Human Traumatic Brain Injury: Microdialysis Studies Using 1, 2-13C2 Glucose. Issue 1 (January 2015) - Jalloh, Ibrahim; Carpenter, Keri L H; Grice, Peter; Howe, Duncan J; Mason, Andrew; Gallagher, Clare N; Helmy, Adel; Murphy, Michael P; Menon, David K; Carpenter, T Adrian; Pickard, John D; Hutchinson, Peter J
Increased 'anaerobic' glucose metabolism is observed after traumatic brain injury (TBI) attributed to increased glycolysis. An alternative route is the pentose phosphate pathway (PPP), which generates putatively protective and reparative molecules. To compare pathways we employed microdialysis to perfuse 1, 2- 13 C2 glucose into the brains of 15 TBI patients and macroscopically normal brain in six patients undergoing surgery for benign tumors, and to simultaneously collect products for nuclear magnetic resonance (NMR) analysis. 13 C enrichment for glycolytic 2, 3- 13 C2 lactate was the median 5.4% (interquartile range (IQR) 4.6–7.5%) in TBI brain and 4.2% (2.4–4.4%) in 'normal' brain ( P <0.01). The ratio of PPP-derived 3- 13 C lactate to glycolytic 2, 3- 13 C2 lactate was median 4.9% (3.6–8.2%) in TBI brain and 6.7% (6.3–8.9%) in 'normal' brain. An inverse relationship was seen for PPP-glycolytic lactate ratio versus Pbt O2 ( r =−0.5, P =0.04) in TBI brain. Thus, glycolytic lactate production was significantly greater in TBI than 'normal' brain. Several TBI patients exhibited PPP—lactate elevation above the 'normal' range. There was proportionally greater PPP-derived lactate production with decreasing Pbt O2 . The study raises questions about the roles of the PPP and glycolysis after TBI, and whether they can be manipulated to achieve a better outcome. This study is the first direct comparison of glycolysis and PPP in human brain.